Obesity, diabetes, hypertension and severe outcomes among inpatients with coronavirus disease 2019: a nationwide study. (January 2022) - Bailly, Laurent; Fabre, Roxane; Courjon, Johan; Carles, Michel; Dellamonica, Jean; Pradier, Christian
Abstract: Objectives: Initial studies of individuals with coronavirus disease 2019 (COVID-19) revealed that obesity, diabetes and hypertension were associated with severe outcomes. Subsequently, some authors showed that the risk could vary according to age, gender, co-morbidities and medical history. In a nationwide retrospective cohort, we studied the association between these co-morbidities and patients' requirement for invasive mechanical ventilation (IMV) or their death. Methods: All French adult inpatients with COVID-19 admitted during the first epidemic wave (February to September 2020) were included. When patients were diagnosed with obesity, diabetes or hypertension for the first time in 2020, these conditions were considered as incident co-morbidities, otherwise they were considered prevalent. We compared outcomes of IMV and in-hospital death according to obesity, diabetes and hypertension, taking age, gender and Charlson's co-morbidity index score (CCIS) into account. Results: A total of 134 209 adult inpatients with COVID-19 were included, half of them had hypertension ( n =  66 613, 49.6%), one in four were diabetic ( n =  32 209, 24.0%), and one in four were obese ( n =  32 070, 23.9%). Among this cohort, IMV was required for 13 596 inpatients, and 19 969 patients died. IMV and death were more frequent in male patients (adjusted oods ratio (aOR) 2.0, 95% CI 1.9–2.1 and aOR 1.5, 95% CI 1.4–1.5, respectively), IMV in patients with co-morbidities (aOR 2.1, 95% CI 2.0–2.2 for CCIS = 2 and aOR 3.0, 95% CI 2.8–3.1 for CCIS ≥5), and death in patients aged 80 or above (aOR 17.0, 95% CI 15.5–18.6). Adjusted on age, gender and CCIS, death was more frequent among inpatients with obesity (aOR 1.2, 95% CI 1.1–1.2) and diabetes (aOR 1.2, 95% CI 1.1–1.2). IMV was more frequently necessary for inpatients with obesity (aOR 1.9, 95% CI 1.8–2.0), diabetes (aOR 1.4, 95% CI 1.3–1.4) and hypertension (aOR 1.7, 95% CI 1.6–1.8). Comparatively, IMV was more often required for patients with the following incident co-morbidities: obesity (aOR 3.5, 95% CI 3.3–3.7), diabetes (aOR 2.0, 95% CI 1.8–2.1) and hypertension (aOR 2.5, 95% CI 2.4–2.6). Conclusions: Among 134 209 inpatients with COVID-19, mortality was more frequent among patients with obesity and diabetes. IMV was more frequently necessary for inpatients with obesity, diabetes and hypertension. Patients for whom these were incident co-morbidities were particularly at risk. Specific medical monitoring and vaccination should be priorities for patients with these co-morbidities. Graphical abstract: Image 1